THE RENAL PATIENT SUPPORT GROUP: SUPPORTING PATIENTS WITH CHRONIC KIDNEY DISEASE THROUGH SOCIAL MEDIA. Issue 3 (28th July 2014) - Muhammad, Shahid; Allan, Michelle; Ali, Filson; Bonacina, Magda; Adams, Meshia
SUMMARY Background The Renal Patient Support Group (RPSG) is a voluntary Facebook group that was developed in 2009 in the UK. The RPSG now has in excess of 5000 members. Objective To highlight the work of the RPSG and to describe how the use of social media has helped raise awareness of chronic kidney disease (CKD). The RPSG offers online peer support internationally, with members sharing their experiences. Methods Since the RPSG is mainly a Facebook platform, this medium has lent itself to raising CKD awareness, also allowing group members to share real‐life stories. Conclusion The RPSG continues to expand and invites health professionals to gain opportunities provided by social media networks to improve the health of their patients by facilitating and getting involved in 'real' discussions.